PEMBERDAYAAN EKONOMI ANGGOTA KOPERASI PEGAWAI ADABIAH (KOPA) PERSPEKTIF PEMBERDAYAAN MASYARAKAT ISLAM - Isra Ahmadi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
Economic empowerment is seen as an effort to build community power by encouraging, motivating, and raising awareness of its economic potential and striving to develop it. This study aims to reveal how the actual economic empowerment carried out by the management of the Adabiah Employee Cooperative (KOPA) towards its members is analyzed based on the perspective of empowering the Islamic community through the takwin or formation stage, the tanzim or development and structuring stage, and the taudi 'stage or the release stage and independence. This article was prepared using a qualitative method through a field study approach. This article contains forms of cooperative management and the obstacles faced by the management in empowering the economies of members of the Adabiah Employee Cooperative (KOPA). This research is expected to be a reference for cooperative administrators, foundation administrators, and empowerment agents in carrying out economic empowerment for cooperative members, employees and the Islamic society.